Orientation nature of the damage-memory effect under triaxial cyclic nonproportional compression of a sandstone - Ivan A. Panteleev; Alexey V. Zaitsev; Konstantin B. Ustinov; Virginia A. Mubassarova; Nikolai I. Shevtsov; Valerii V. Khimulia; Vladimir I. Karev; Yurii F. Kovalenko (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2022)
The paper describes the mechanisms and conditions for the damage-memory effect (Kaiser effect) in rocks subjected to a three-dimensional nonproportional cyclic loading with changes in the rocks' shape and orientation of the Lam-ellipsoid. The experiments with the cubic samples taken from polymictic sandstone were conducted on Triaxial Independent Loading Testing System with continuous recording of an acoustic emission signals. The results of a nonproportional triaxial compression under the developed protocol, it is 9-cycle loading program, have shown that a dominate mechanism of the damage-memory effect in each ensemble of cracks (vectored differently) is the development of micro-cracks of opening fracture mode oriented subnormally to the minimum main stress. It was found that the Kaiser damage-memory effect is detected not so much to the fact of opening cracks, friendly oriented, as to a discrete growing (increase of length) of already existing and newly emerging micro-cracks. The obtained results can be considered as a trigger for models development oriented to strain and destruction of rocks, taking into account the anisotropic nature of damage accumulation.